2014
DOI: 10.1007/s11936-014-0300-y
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function Testing in Contemporary Clinical and Interventional Practice

Abstract: Dual antiplatelet therapy with a combination of aspirin and an inhibitor of the ADP P2Y12 receptor is the recommended treatment for patients with acute coronary syndrome or who are undergoing percutaneous coronary intervention (PCI). However, patients may continue to have ischemic recurrences, including stent thrombosis, which have been linked with the well-known variability in individual response to antiplatelet therapy, and clopidogrel in particular. There are currently several assays available to measure pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 90 publications
0
37
0
Order By: Relevance
“…46,69,70 Although a detailed description of these trials is beyond the scope of this manuscript, several drawbacks that are likely to have made a large contribution to the reported findings should be highlighted, most importantly the low clinical risk profile of the patient populations enrolled in these trials. 71 Ongoing randomized studies to assess the use of novel P2Y 12 -receptor therapies on the basis of results of pharma codynamic testing, such as the TROPICAL-ACS trial, 72 and genetic testing, such as the POPular Genetics trial, 73 in patients with ACS undergoing PCI, will provide more insights into this topic.…”
Section: Results From Pharmacodynamic Investigationsmentioning
confidence: 99%
“…46,69,70 Although a detailed description of these trials is beyond the scope of this manuscript, several drawbacks that are likely to have made a large contribution to the reported findings should be highlighted, most importantly the low clinical risk profile of the patient populations enrolled in these trials. 71 Ongoing randomized studies to assess the use of novel P2Y 12 -receptor therapies on the basis of results of pharma codynamic testing, such as the TROPICAL-ACS trial, 72 and genetic testing, such as the POPular Genetics trial, 73 in patients with ACS undergoing PCI, will provide more insights into this topic.…”
Section: Results From Pharmacodynamic Investigationsmentioning
confidence: 99%
“…The use of genetic testing as a tool to incorporate into routine clinical practice is also challenged by the fact that a parallel line of research focused on personalizing antiplatelet therapy based on results of platelet function testing has provided thus far disappointing results [121124]. In fact, although observational studies in high-risk PCI settings have shown that modification of antiplatelet therapy based on results of platelet function studies are associated with favorable outcomes, these findings have not been corroborated within a number of randomized clinical trials [125]. It may be argued that these trials were flawed by target population, antiplatelet medications, platelet function assay, HPR cut-off values, timing of testing, among other variables, which were not adequate to test for the study hypothesis [125].…”
Section: Expert Commentarymentioning
confidence: 99%
“…Although randomized clinical trials evaluating the use of platelet function testing to tailor antiplatelet therapy have failed to demonstrate any benefit, the main limitation of all these studies was the inclusion of low-risk populations. 20 The results of the study by Baber et al 15 clearly identify a subset of patients where further risk-markers may potentially help stratify patients to optimize antithrombotic therapy. Indeed, additional prospective studies are needed to better evaluate this hypothesis.…”
Section: See Article By Baber Et Almentioning
confidence: 99%